1997
DOI: 10.1021/ic970079h
|View full text |Cite
|
Sign up to set email alerts
|

Intercalative Ion Exchange of Polyamine Transition Metal Complexes into Hydrogen Uranyl Phosphate

Abstract: A series of derivatives of hydrogen uranyl phosphate (HUP) was prepared by displacing the butylammonium ions of butylammonium uranyl phosphate with the transition metal complexes Cu(en)(2)(2+), Cu(pn)(2)(2+), Cu(trien)(2+), Cu(14-ane)(2+), Cu(15-ane)(2+), Ni(trien)(2+), Ni(14-ane)(2+), and Ni(diene)(2+). X-ray powder patterns proved that the original tetragonal structure of the UP layers remained intact in all derivatives. The extent of the ion exchange and the interlamellar distances were found to depend main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In addition, certain uranyl compounds such as hydrogen uranyl phosphate (HUP) [40][41][42][43] and Cs 4 [(UO 2 ) 2 (V 2 O 7 )O 2 ] [44] have been shown to exhibit high cationic conductivities. In order to evaluate the potential for ion-exchange reactions of alkali metal cations with 1, samples were equilibrated with 0.01 M solutions of NaCl/NaOH, KCl/KOH, or CsCl/CsOH.…”
Section: Ion-exchange Studiesmentioning
confidence: 99%
“…In addition, certain uranyl compounds such as hydrogen uranyl phosphate (HUP) [40][41][42][43] and Cs 4 [(UO 2 ) 2 (V 2 O 7 )O 2 ] [44] have been shown to exhibit high cationic conductivities. In order to evaluate the potential for ion-exchange reactions of alkali metal cations with 1, samples were equilibrated with 0.01 M solutions of NaCl/NaOH, KCl/KOH, or CsCl/CsOH.…”
Section: Ion-exchange Studiesmentioning
confidence: 99%
“…Based on these new structures, the topological relations can be discerned [5] and used as a basis for materials design yielding solids with specific properties: e.g. selective ion-exchange [6][7][8][9][10][11][12], mixed-valency [13,14], ionic conductivity [15][16][17][18][19][20], enhanced fluorescence [21][22][23], magnetic ordering [11,24], non-linear optical properties [12,25], and differential gas absorption [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Clearfield and co-workers have demonstrated that in the synthesis of uranyl phosphonates, the presence of sterically demanding organic groups on the phosphonate ligands leads to the formation of novel structure types, including porous structures. Second, these materials may be envisioned to exhibit useful catalytic, ion-exchange, and intercalation properties. For example, hydrogen uranyl phosphate (HUP) is a fast hydrogen ion conductor and a versatile ion-exchange reagent, and Hutchings et al recently demonstrated that uranium oxide-based materials are effective oxidation catalysts for the destruction of a range of hydrocarbon- and chlorine-containing industrial pollutants . Finally, the existence of a number of stable oxidation states of actinides, such as uranium, offers the possibility of synthesising materials with useful optical and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%